Respostas
respondido por:
2
8y-2=2y+10
8y-2y= 10+2
6y= 12
y=12/6
y=2
8y-2y= 10+2
6y= 12
y=12/6
y=2
respondido por:
0
1 passo organize a equação.
8y-2=2y+10 -> 8y-2y=10+2
2 passo resolva como uma equação de primeiro grau.
8y-2y=10+2 --> 6y=12 --> y=12/6-> y=2
8y-2=2y+10 -> 8y-2y=10+2
2 passo resolva como uma equação de primeiro grau.
8y-2y=10+2 --> 6y=12 --> y=12/6-> y=2
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás